Strategies for Improving Peptide Stability and Delivery - Othman Al Musaimi; Lucia Lombardi; Daryl R. Williams; Fernando Albericio (Pharmaceuticals, 2022)
Peptides play an important role in many fields, including immunology, medical diagnostics, and drug discovery, due to their high specificity and positive safety profile. However, for their delivery as active pharmaceutical ingredients, delivery vectors, or diagnostic imaging molecules, they suffer from two serious shortcomings: their poor metabolic stability and short half-life. Major research efforts are being invested to tackle those drawbacks, where structural modifications and novel delivery tactics have been developed to boost their ability to reach their targets as fully functional species. The benefit of selected technologies for enhancing the resistance of peptides against enzymatic degradation pathways and maximizing their therapeutic impact are also reviewed. Special note of cell-penetrating peptides as delivery vectors, as well as stapled modified peptides, which have demonstrated superior stability from their parent peptides, are reported.